The Effect of Pre-Damaged Level on Repair Damaged Columns by Using Steel Straps Tensioning Technique - Mohd Apandi, Nazirah; Khun Ma, Chau; Loong Chin, Chee; Zawawi Awang, Abdullah; Omar, Wahid (International Journal of Engineering and Technology, 2018)
To date, repair of damaged columns has become increasingly more significant. The failure of columns structure contributes to the serious consequences in structural stability. Most of the existing repairing techniques are based on lateral passive confining pressure. However, this passive-type of confinement is ineffective in restoring the performance of damaged concrete columns. In this regards, active confinement was selected in this study to repair damaged concrete columns which can actively confine concrete in this study. Steel strapping tensioning technique (SSTT) allows pre-tensioning low-cost recycled steel straps around the damaged column was chosen herein to represent active confinement. A total of 12 columns were prepared and loaded axially to certain degree of their respective ultimate strength. Hence, a pre-damage level of the columns was developed. Then, the damaged columns repaired by using mortar and confined with SSTT. Finally, the repaired columns were then tested under monotonic uniaxial load. The structural performances of the confined repaired columns were compared with those of the repaired columns without confinement. It is expected that as the concrete compressive strength increases, the effectiveness in restoring the load carrying capacity of the damaged column becomes more significant. Â Â